Hierarchical Porous ZnMn2O4 Microspheres as a High-Performance Anode for Lithium-Ion Batteries. (20th September 2016) - Fan, Binbin; Hu, Aiping; Chen, Xiaohua; Zhang, Shiying; Tang, Qunli; Wang, Jiande; Deng, Weina; Liu, Zheng; Xiao, Kuikui
Abstract: The hierarchical porous ZnMn2 O4 microsphere is successfully synthesized by a facile ultrasonic spray pyrolysis technology combined with the thermal annealing treatment in air. The porous microspheres are built from interconnected porous nanosheets which are composed of numerous nanoparticles with size of approximately 15 nm. This unique structure could not only facilitate the transfer of ions and electrons, but also accommodate large volume expansion and contraction so that it shows excellent electrochemical performance. When used as anode materials for lithium ion batteries (LIBs), the ZnMn2 O4 porous microspheres exhibited a discharge capacity of 1044 mA h g −1 after 300 cycles at a current of 500 mA g −1 and superior rate capability (859 mA h g −1 at 2000 mA g −1 ). The highly porous structure with nanosheet networks composed of nanoparticles is responsible for the enhanced performance.